If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9(x + -3) = -3(-2x + 4) Reorder the terms: 9(-3 + x) = -3(-2x + 4) (-3 * 9 + x * 9) = -3(-2x + 4) (-27 + 9x) = -3(-2x + 4) Reorder the terms: -27 + 9x = -3(4 + -2x) -27 + 9x = (4 * -3 + -2x * -3) -27 + 9x = (-12 + 6x) Solving -27 + 9x = -12 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -27 + 9x + -6x = -12 + 6x + -6x Combine like terms: 9x + -6x = 3x -27 + 3x = -12 + 6x + -6x Combine like terms: 6x + -6x = 0 -27 + 3x = -12 + 0 -27 + 3x = -12 Add '27' to each side of the equation. -27 + 27 + 3x = -12 + 27 Combine like terms: -27 + 27 = 0 0 + 3x = -12 + 27 3x = -12 + 27 Combine like terms: -12 + 27 = 15 3x = 15 Divide each side by '3'. x = 5 Simplifying x = 5
| 3(2y-8)=6 | | 6y^2+12y+13=2y^2+4 | | -2x^2-19x+35=0 | | -x+5.6=-7.4 | | 6x^2+13x=28 | | 3b^2+9b-30=0 | | 5j+12k=22 | | 2q^2+22q=-60 | | P+5.7=-19.5 | | -108-7x=7x+18 | | 2p*5p= | | 5x+23=13x-57 | | 76-5x=40x+21 | | 2x^2+4x-30=0 | | 280=(2)(5)(4) | | 6v^2-7v=24 | | 4y^2=25 | | 7n=3n+8 | | 2c^2-7c=-5 | | 2x+7=-4x-16 | | 2m-61=73 | | 2x+5=85-6x | | 86-7x=38x+16 | | 11=-2z+8 | | t^2-3t=28 | | 11-10x=77-24x | | 7j+3k=17 | | 2n^2-11n=51 | | 15=3+6x | | x^2+10x+4=10 | | 3x+7=-26-8x | | 5z^2+6z+14=0 |